Pelatihan Pemanfaatan Produk Oleofood Sawit Pada Industri Perhotelan dan UMKM - Suwintari, I Gusti Ayu Eka; Wirawan, Putu Eka; Iswara, Agus Made Yoga (Jurnal Pemberdayaan Pariwisata; Vol 7 No 1 (2025): Jurnal Pemberdayaan Pariwisata, 2025)
The training on the utilization of palm-based oleofood products aims to enhance the knowledge and skills of hospitality industry professionals and UMKM (Micro, Small, and Medium Enterprises) in producing innovative, healthy, and sustainable culinary products. The program includes educational workshops, product demonstrations, and hands-on practice sessions, featuring spaghetti carbonara, chicken soup (soto ayam), and klepon coffee made with oleofood. Palm-based oleofood offers advantages such as high heat stability, improved food texture and taste, and better nutritional value. Attended by 90 participants from diverse backgrounds, the training highlights strong interest in food diversification and the use of sustainable local ingredients. Participants were also equipped with practical knowledge to address common challenges such as limited access to quality raw materials and public skepticism about palm-based products. This training contributes to enhancing the competitiveness of the local culinary industry and encourages broader adoption of palm-based innovations. Keywords:  palm oleofood, culinary innovation, UMKM training